The remarried empress. 4 - Alphatart (Novelist); HereLee (Mangaka) (HereLee (Mangaka). Jaehon hwanghu., 2023)
"Sovieshu's lover, his mistress, and the future mother of his child--Rashta's got it all--on the surface, that is. What she really wants is to be able to keep herself and the baby safe on her own, regardless of whether she has the favor of the emperor. The largest obstacle standing in her way? Navier, or so she believes. And when her sole confidant, Duke Ergi, advises her that the best defense is a good offense, Rashta comes to realize exactly what it is she must do. This is Rashta's world, and everyone else is just living in it" -- Back cover.